Gratification Prevention and Control in PT PJB Ubjom Pacitan - Agiyanto, Ucuk; Febriana, Lila Afrida (International Journal of Law and Society, 2022)
The practice of gratification has become commonplace in the corporate environment. A Gratification Control Unit was formed within PT PJB UBJOM Pacitan to prevent gratification practices. With the establishment of the Gratification Control Unit, it is hoped that it can prevent and control gratification practices at PT PJB UBJOM Pacitan which incidentally is one of the subsidiaries of the State Electricity Company, which is part of the State-Owned Enterprises. This study aims to explain the basis of gratification control within the company and how gratification control is practised at PT PJB UBJOM Pacitan. This study uses a normative and empirical juridical approach, which is the relationship between statutory provisions and the implementation mechanism in the company. Prevention and control efforts have been carried out by establishing a code of conduct between employees and stakeholders inside and outside the company. The field that plays a role in this gratification action is MMR (Quality and Risk Management), with socialization among parties within the company.